Pengaruh Capital Intensity, Karakteristik Perusahaan, Dan CSR Disclosure Terhadap Penghindaran Pajak Pada Perusahaan Manufaktur - Anita Ade Rahma; Nila Pratiwi; Hilda Mary; Indriyenni Indriyenni (Politeknik Ganesha Medan, 2022)
This study aims to determine the effect of capital intensity, company characteristics, and disclosure of corporate social responsibility on tax avoidance with leverage as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange in the period 2015-2017. The sample in this study was taken by purposive sampling method in manufacturing companies listed on the Indonesia Stock Exchange in the period 2015-2017. The number of samples used was 82 companies. The method of analysis of this study is multiple linear regression using eviews 9. The results showed that the intensity of capital had a positive and significant effect on tax avoidance, the company's characteristics had a negative and significant effect on tax avoidance, the disclosure of corporate social responsibility had a positive effect and not significant impact on tax avoidance. Leverage is able to moderate the influence of capital intensity on tax avoidance, leverage is able to moderate the effect of corporate characteristics on tax avoidance while leverage is not a variable that is able to moderate the disclosure effect of corporate social responsibility on tax avoidance. Finally, the authors suggest that tax avoidance considerations can be used other than those used by researchers. For the calculation of capital intensity, company characteristics, and disclosure of CSR can use other proxy proxies other than those used by researchers. And for the next researcher, it is expected to be able to add variables related to the variables affected, and extend the research period.